Comparative Analysis of Interval, Skipped, and Key-vertebral Pedicle Screw Strategies for Correction in Patients With Lenke Type 1 Adolescent Idiopathic Scoliosis. Issue 10 (March 2016) - Wang, Fei; Xu, Xi-Ming; Lu, Yanghu; Wei, Xian-Zhao; Zhu, Xiao-Dong; Li, Ming
Abstract : Abstract: Pedicle screw constructs have become the mainstay for surgical correction in patients with spinal deformities. To reduce or avoid the risk of pedicle screw-based complications and to decrease the costs associated with pedicle screw instrumentation, some authors have introduced interval, skipped, and key-vertebral pedicle screw strategies for correction. However, there have been no comparisons of outcomes among these 3 pedicle screw-placement strategies. The aim of this study was to compare the correlative clinical outcomes of posterior correction and fusion with pedicle screw fixation using these 3 surgical strategies. Fifty-six consecutive patients with Lenke type 1 adolescent idiopathic scoliosis were included in this study. Twenty patients were treated with the interval pedicle screw strategy (IPSS), 20 with the skipped pedicle screw strategy (SPSS), and 16 with the key-vertebral pedicle screw strategy (KVPSS). Coronal and sagittal radiographs were analyzed before surgery, at 1 week after surgery, and at the last follow-up after surgery. There were no significant differences among the 3 groups regarding preoperative radiographic parameters. No significant difference was found between the IPSS and SPSS groups in correction of the main thoracic curve (70.8% vs 70.0%; P = 0.524). However, there were statistically significant differences between the IPSS and KVPSS groups (70.8% vs 64.9%) and between the SPSS and KVPSS groups (70.0% vs 64.9%) in correction of the main thoracic curve ( P < 0.001 for both). Additionally, there were no significant differences among the 3 strategies for sagittal parameters at the immediate postoperative and last postoperative follow-up periods, though there were significant differences in the Cobb angle between the preoperative and immediate postoperative periods among the 3 groups, but not between the immediate postoperative and last follow-up periods. The amount of hospital charges in the SPSS group was significantly higher than those in the IPSS ( P < 0.001) and KVPSS groups ( P < 0.001). There were also significant differences in operative time between the IPSS and KVPSS groups ( P < 0.001) and between the SPSS and KVPSS groups ( P < 0.001). Each of the 3 types of pedicle screw strategies for correction in patients with Lenke type 1 adolescent idiopathic scoliosis are effective, with satisfactory coronal and acceptable sagittal plane results. Although the KVPSS does not provide superior operative correction compared with the IPSS and SPSS, it can achieve a satisfactory clinical outcome and is more cost-effective.